DAMPAK PENERAPAN MANAJEMEN LABA TERHADAP KINERJA SAHAM PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi empiris pada perusahaan sektor perbankan yang terdaftar di BEI periode 2013 - 2017) - B2041162002, DEVIA INDAH YANUARTI (Universitas Tanjungpura, 2019)
This research is intended to find out the impacts of the implementation of profit management through Real Earnnings Management (REM) proxy and Accrual Earnings Management (AEM) proxy towards the mechanism o a compan's share in Indonesia Stock Exchange. The moderation variable used in the research is Good Corporate Governance (GCG) which involve Auditing Committee, Independent Commissioner, Institution Ownership, Managerial Ownership.The population in this research are companies in banking sector which are registered at Indonesia Stock Exchange from 2013 until 2017. The method used in sampling is purposive sampling. Therefore, the number of sample companies is 98 following the purposive sampling.The method used in this researched is multiple regression, and the result of research show that (1) REM has effect on the company 's share mechanism, (2) AEM has no effect on the company 's share mechanism, (3) Investors' decisions are not influenced by the company 's total asset, (4) GCG has negative moderation on REM, (and (5) GCG has no moderation on AEM.Â Keywords : Earnings Management, Earnings Manipulation, Stock Performance, Banking Stock Performance, Good Corporate Governance, GCG